“A critical appraisal of traditional pottery in Ghana - a look at the cultural environment” - Clottey, Samuel Marcus C. (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of Postgraduate Diploma in Industrial Management.